Contemporary carbene chemistry - Moss, Robert A. (Wiley series of reactive intermediates in chemistry and biology, 2014)
"The newfound stability of carbenes has led to their development as catalysts and ligands for metal complexes of vast potential, including biomolecule labeling and surface modification of materials. Providing a fresh evaluation of the field, Contemporary Carbene Chemistry explores novel structural, catalytic, and organometallic aspects of carbene chemistry. Chapters focus on the most interesting, fruitful, and promising directions in their topical areas. Featuring a chapter by Nobel Laureate Robert Grubbs, this timely text provides graduate students with the most innovative and promising aspects of carbene research over the past decade"--